VITRECTOMY WITH EPIRETINAL MEMBRANE PEELING ALONE VERSES COMBINED WITH INTERNAL LIMITING MEMBRANE PEELING FOR IDIOPATHIC EPIRETINAL MEMBRANE - Jatoi, Asadullah; Shaikh, Fahad Feroz; Rehman, Aziz ur (Journal of Ayub Medical College Abbottabad, 2020)
Background: The objective of this study was to determine and compare the structural and functional outcome in eyes who underwent Pars Plana Vitrectomy (PPV) with Epiretinal Membrane (ERM) peeling alone verses combined Epiretinal membrane with Internal Limiting Membrane (ILM) peeling for Idiopathic Epiretinal Membrane along with rate of recurrence. Methods: It was an interventional randomized study, conducted at Al-Ibrahaim Eye Hospital, Malir, Karachi, for two-year period from 1st August 2016 to 1st August 2018. A total of forty-four eyes of 44 patients were divided into two group equally. Group A contains 22 eyes of 22 patients who underwent PPV with ERM peeling alone. Group B also contains 22 eyes of 22 patients who underwent PPV with ERM and ILM peeling. The follow up period was 1 year. The patients having best corrected visual acuity (BCVA) less than 6/18 or symptom of metamorphopsia were included in our study. The best corrected visual acuity (BCVA) and central macular thickness (CMT) were recorded at 3, 6 and 12-month follow up. Results: In group A, the mean preoperative BCVA was 0.148 Log MAR (6/36 Snellen chart). The mean postoperative BCVA at 3, 6, and 12 months was 0.32 (6/18), 0.49 (6/12 P) and 0.50 (6/12), respectively. In group B, the mean preoperative best corrected visual acuity was 0.161 Log MAR (6/36 P Snellen chart). The mean postoperative BCVA at 3, 6, and 12 months was 0.36 (6/18 P), 0.51 (6/12) and 0.51 (6/12) respectively. The mean preoperative Central Macular Thickness (CMT) was 398.9 Î¼m in group A and 384.7 Î¼m in group B. The mean CMT in group A was 271.4, 236.7 and 229.8 Î¼m at 3, 6 and 12 months, respectively. In group B, the mean CMT was 272.1, 233.8 and 220.4 Î¼m at 3, 6 and 12 months, respectively. No significant difference was found in visual outcome and central macular thickness between two groups. Conclusion: Pars plana vitrectomy along with ERM peeling alone or combined with ILM peeling is safe procedure. Both methods were effective functionally and structurally in treatment of idiopathic ERM, however no significant difference and no recurrence of ERM was observed in either group. Keywords: Epiretinal membrane; Pars Plana Vitrectomy; best corrected visual acuity; central macular thickness